Sistem Informasi E-Commerce Excelsa Coffee Shop Berbasis Web - Steven Franjaya; Elisawati Elisawati; Rahmat Hidayatullah; Nur Rubiati (STMIK KAPUTAMA, 2023)
Excelsa Coffee Shop is one of the businesses engaged in culinary in the form of a cafe located in Dumai. In the sales process so far at Excelsa Coffee Shop, it is done manually / offline by directly coming to the store. The problem that occurs from the manual system is the absence of sales reports per day or per month, a service system that still relies on a manual system is also not much profitable in sales because it depends on customers who buy directly from the store so that the sales process and results are less efficient. Therefore, a computerized system is needed to help the sales process and record sales results online, namely, E-commerce.E-commerce is an online-based sales system that is used to view and buy products through the website, by first having an account by registering, after having an account customers can check out and make payments via bank transfer or cash on delivery (COD).